2016
DOI: 10.1093/brain/aww072
|View full text |Cite
|
Sign up to set email alerts
|

Reasoning by analogy requires the left frontal pole: lesion-deficit mapping and clinical implications

Abstract: SEE BURGESS DOI101093/BRAIN/AWW092 FOR A SCIENTIFIC COMMENTARY ON THIS ARTICLE  : Analogical reasoning is at the core of the generalization and abstraction processes that enable concept formation and creativity. The impact of neurological diseases on analogical reasoning is poorly known, despite its importance in everyday life and in society. Neuroimaging studies of healthy subjects and the few studies that have been performed on patients have highlighted the importance of the prefrontal cortex in analogical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 111 publications
5
41
0
2
Order By: Relevance
“…The FPN is thought to be responsible for the moment-to-moment implementation of cognitive task goals (Cocchi, Zalesky, Fornito, & Mattingley, 2013;Dosenbach et al, 2007). Damage to frontal and parietal cortices has also been associated with poorer performance in tests of cognitive reasoning (Urbanski et al, 2016;Woolgar et al, 2010). In line with this, our results suggest that in CCD individuals FPN activity does not modulate in the manner required to solve complex cognitive problems.…”
Section: Discussionsupporting
confidence: 76%
“…The FPN is thought to be responsible for the moment-to-moment implementation of cognitive task goals (Cocchi, Zalesky, Fornito, & Mattingley, 2013;Dosenbach et al, 2007). Damage to frontal and parietal cortices has also been associated with poorer performance in tests of cognitive reasoning (Urbanski et al, 2016;Woolgar et al, 2010). In line with this, our results suggest that in CCD individuals FPN activity does not modulate in the manner required to solve complex cognitive problems.…”
Section: Discussionsupporting
confidence: 76%
“…Left lateral patients were impaired even with good working memory but this was not the case for the other frontal groups. Recently, Urbanski et al (2016) used analogy tasks which are somewhat simpler than fluid intelligence tests, yet require abstraction. Patients were requested to find an analogy between a source set and one of two candidate sets of coloured letters of varying size.…”
Section: Forms Of Active Thought Abstractionmentioning
confidence: 99%
“…Non-local effects of lesions have previously been explored using various forms of atlas-based analyses of tract damage [23][24][25][26][27][28][29][30][31][32], lesion-driven tractography [32][33][34], disconnectomemapping [35][36][37][38][39] and lesion-driven resting state fMRI (rs-fMRI) connectivity [34,40].…”
Section: Behaviourmentioning
confidence: 99%
“…The dysfunction of distant areas that are connected to the lesioned tissue has also been reported in fMRI studies. They have shown that the networks are disrupted even by distant lesions through disconnection and diaschisis mechanisms [20][21][22].Non-local effects of lesions have previously been explored using various forms of atlas-based analyses of tract damage [23][24][25][26][27][28][29][30][31][32], lesion-driven tractography [32][33][34], disconnectomemapping [35][36][37][38][39] and lesion-driven resting state fMRI (rs-fMRI) connectivity [34,40].However, determining what these methods actually measure and identifying how to properly combine them are not always fully clear to the scientific community. Furthermore, there is an extremely limited availability of free, open-source software that applies methods to measure the non-local effects of lesions.…”
mentioning
confidence: 99%